Penguatan Fungsi Pengawasan Pemerintah Kota/Kabupaten Dalam Penggunaan E-money Brizzi Sebagai Alat Bayar Retribusi di Sumatera Barat - Andora, Hengki; Gusminarti, Gusminarti; Romi, Romi; Siagian, Abdhy Walid (Nagari Law Review, 2023)
Levies are a source of original regional income as regulated in Article 285 Paragraph (1) of Law Number 23 of 2014 concerning Regional Government. The authority to collect levies is regulated in Article 23A of the 1945 Constitution, then implemented by Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. So far, retribution collection has been carried out in cash, and along with technological developments, this method is no longer suitable, so it has been replaced with electronic money. This provision is based on Bank Indonesia Regulation Number 20/6/PBI 2016 concerning E-Money and is reinforced by the Circular Letter of the Minister of Home Affairs Number 901/1866/SJ /2017 which regulates the Implementation of Non-Cash Transactions and Presidential Instruction Number 10 of 2016 concerning Prevention and Eradicating Corruption. West Sumatra, as one of the provinces in Indonesia, has implemented the use of E-Money facilities in 2019 through E-Money Brizzi issued by Bank Rakyat Indonesia. It's just that in practice there are deviations in implementation so that we don't get maximum results. In connection with this, the author conducted research with the title "Strengthening the Supervision Function of the Use of Brizzi E-money as a Means of Paying City/Regency Levy Fees in West Sumatra". The areas used as samples. research is Padang City, Pariaman City, and Bukittinggi City with the main problems being researched. How to strengthen the monitoring function regarding the use of e-money Brizzi as a means of paying levies in cities/regencies in West Sumatra? From the research results, strengthening the monitoring function of the use of E-Money Brizzi in City/Regency governments in West Sumatra can be carried out by the parties, namely BRI as the Issuer of E-Money Brizzi and Bapenda as the user of the E-Money Brizzi facility in collecting levies. Meanwhile, the problems found in strengthening the supervisory function for the use of these facilities are incomplete regulations as a legal umbrella to serve as technical guidance in monitoring the use of facilities at each collection agency, and there is still a lack of education and outreach to the public by the parties.